Overview of the Dental Caries of Students at MTS Muhzirah Galesong Selatan Takalar Regency - Saputra, Andreawan Bayu; Maulida, Nurul Safira; Rabiah, Khadijatul; Kurniati Tory, Rani Tri; Salsabilla, Shinta Aulia; Gabriyel Ananda; Ramadhani Rahman, Raihana Nur; Rahmani, Dini; Firman, Firman; Ayu Yuniar, Ainun (Journal of Applied Oral Health and Dental Therapy (JAOHDT), 2026)
Background: Dental caries is one of the most prevalent oral health problems, particularly among adolescents. Objective:This study aimed to describe the dental caries status of students at MTs Muhzirah Galesong Selatan. Methods: The research design used was quantitative descriptive. The study was conducted in Bontokassi Village, South Galesong District, Takalar Regency, in September 2025, involving 19 respondents selected using a purposive sampling technique. Data were collected through questionnaires and structured interviews, and analyzed using IBM SPSS Statistics with univariate and bivariate analysis. Results:The results showed that most respondents were male (57.8%), with the highest proportion aged 17 years (36,8%). The prevalence of dental caries was 57.8%, with a higher proportion in males (36,8%) compared to females (21%). Based on age distribution, caries cases were found across all age groups with relatively similar patterns. Conclusion: In conclusion, the prevalence of dental caries among students at MTs Muhzirah Galesong Selatan, Takalar Regency is relatively high. Therefore, continuous promotive and preventive efforts are needed to improve oral health status among adolescents.